Child characteristics and early intervention referral and receipt of services: a retrospective cohort study - Beth M. McManus; Zachary Richardson; Margaret Schenkman; Natalie J. Murphy; Rachel M. Everhart; Simon Hambidge; Elaine Morrato (BMC, 2020)
Abstract Background Early Intervention (EI) is a federally mandated, state-administered system of care for children with developmental delays and disabilities under the age of three. Gaps exist in the process of accessing EI through pediatric primary care, and low rates of EI access are well documented and disproportionately affect poor and minority children. The aims of this paper are to examine child characteristics associated with gaps in EI (1) referral, (2) access and (3) service use. To our knowledge, this is the first study to leverage linked safety net health system pediatric primary care and EI records data to follow EI-referred children longitudinally to understand EI service use gaps from EI referral to EI service utilization. Methods In a retrospective cohort design (14,710 children with developmental disability or delay), we linked pediatric primary care records between a large, integrated safety net health system in metro Denver and its corresponding EI program (2014-2016). Using adjusted marginal effects [ME, (95% CI)], we estimated gaps in EI referral, access, and service type (i.e., physical [PT], occupational [OT], speech therapy [ST] and developmental intervention [DI]). Analyses accounted for child characteristics including socio-demographics, diagnosis, condition severity, and baseline function. Results Only 18.7% of EI-eligible children (N = 2726) received a referral; 26% of those (N = 722) received services for a net enrollment rate of 5% among EI-eligible children. Having the most severe developmental condition was positively associated with EI referral [ME = 0.334 [0.249, 0.420]) and Individualized Family Services Plan (IFSP) receipt [ME = 0.156 [0.088, 0.223]). Children less likely to be EI-referred were Black, non-Hispanic (BNH) [ME = -0.029 (− 0.054, − 0.004)] and had a diagnosed condition ([ME = − 0.046 (− 0.087, − 0.005)]. Children with a diagnosis and those with higher income were more likely to receive PT or OT. Higher baseline cognitive and adaptive skills were associated with lower likelihood of PT [ME = -0.029 (− 0.054, − 0.004)], OT [ME = -0.029 (− 0.054, − 0.004)], and ST [ME = -0.029 (− 0.054, − 0.004)]. Conclusions We identified and characterized gaps in EI referral, access, and service use in an urban safety-net population of children with high rates of developmental delay. Interventions are needed to improve integrated systems of care affecting primary care and EI processes and coordination.